Randomized Controlled Clinical Trial to Examine the Efficacy of Oral Midazolam in Post Operative Pain Reduction in Patients Undergoing Laparoscopic Cholecystectomy - Farah Batool Siddiqui, M. Farooq Umer, Hiba Moazzam, Sarosh, Umar Soomro, Shahtaj Adil Shah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Stressful conditions like surgery and anesthesia trigger neuroendocrine pathway activation, which can have dangerous hemodynamic effects on the patient. One method for minimizing these hemodynamic consequences is maintaining an optimum level of anesthesia. Another option is giving patients a pharmaceutical formulation that modifies how anesthetic agents react. Objective: The current study sought to determine if preoperative oral midazolam could reduce postoperative pain scores and the occurrence of Rescue Analgesia in patients undergoing laparoscopic cholecystectomy. Methods: This is a single-blinded randomized controlled study conducted at the Surgery department of Jinnah Medical College Hospital, Korangi Karachi, on patients undergoing laparoscopic cholecystectomy. Through simple random sampling, participants were divided into two study groups, control (n=32) and 7.5mg receiving preoperative oral midazolam-intervention group. After surgery, the VAS pain score in both group participants was measured at 2, 8, 12, and 24 hours. The frequency of rescue analgesia and duration of hospital stay was also observed. Standard deviation, mean, chi-square test, and T-test was performed to determine the variation in both groups by using SPSS version 26. The P value ≤0.005 was measured significant. Results: No significant difference in the postoperative pain score after oral administration of midazolam in the intervention group compared to the control group at 2, 12, and 24 hrs intervals. Except at 8-hour intervals, a significant change of 0.004 was observed in both study groups. A significant variation of 0.008 was observed in the duration of hospital stay in the intervention group when compared with the control group. Lastly, in the present study, no significant difference in the frequency of rescue analgesics was observed in both study groups. Practical implication: This study will help out to determine the right dosage of oral midazolam which might effectively be used in managing post-operative pain in laparoscopic cholecystectomy patients. Conclusion: Orally administeredmidazolam was not efficient in lowering the pain score in patients undergoing laparoscopic cholecystectomy. Keywords: Midazolam, Post-operative pain, Laparoscopic cholecystectomy, Local anesthetics